Characterization of forebrain neurons derived from late-onset Huntington's disease human embryonic stem cell lines - Niclis, Jonathan C.; Pinar, Anita; Haynes, John M.; Alsanie, Walaa; Jenny, Robert; Dottori, Mirella; Cram, David S. (Frontiers in Cellular Neuroscience, 2013)
Huntington's Disease (HD) is an incurable neurodegenerative disorder caused by a CAG repeat expansion in exon 1 of the Huntingtin gene. Recently, induced pluripotent stem cell lines carrying atypical and aggressive (CAG60+) HD variants have been generated, and perplexingly exhibit disparate molecular pathologies. Here we investigate two human embryonic stem cell (hESC) lines carrying CAG37 and CAG51 repeats to assess whether typical late-onset expansions exhibit HD pathologies. HD hESC properties were assessed in comparison to wildtype control lines at undifferentiated states and throughout forebrain neuronal differentiation. Pluripotent HD lines demonstrate growth, viability, pluripotent gene expression, mitochondrial activity and forebrain specification that is indistinguishable from control lines. Expression profiles of crucial genes known to be dysregulated in HD remain unperturbed in the presence of mutant protein and throughout differentiation; however, elevated glutamate responses were observed in HD CAG51 neurons. These findings suggest typical late-onset HD mutations do not alter pluripotent parameters or differentiation mechanics but that neuronal progeny may possess the capacity to recapitulate neuropathologies seen in human patients. Such HD models will help further our understanding of the cascade of pathological events leading to disease onset and progression, while simultaneously facilitating the identification of candidate HD therapeutics.